Body Condition Factor for Broad-snouted Caiman, Caiman latirostris (Daudin, 1802) - Ciocan, Hernán (2024)
The Fulton coefficient (K) is an index of body condition that relates length and weight, indicates relative fatness and was designed to determine growth in fish. Various animal studies employ the Body Condition Factor (BCF) as a metric to assess the physical well-being of an individual. This index enables the inference of an individual’s relationship with the environmental conditions and its growth. In addition, the BFC is used to compare populations across various locations or to examine how some unique animal population, such as of crocodilians, varies over time. However, the index value is not attributed to individuals and its only employed to compare K values among them. In this study, our aim was to generate reference values for the K index to classify individuals of Caiman latirostris according to their physical condition. We did this by categorizing individuals as skinny, good or fat and, then associating them to their respective K values to further establish a K range that relates with the physical condition of the species. We then conducted non-parametric tests to determine the fit of K values to the classification. These results can serve as reference values for individual conditions for the species, and would be of use in several population studies.